A resistência ao currículo de história para o ensino médio prescrito pela Secretaria de Estado da Educação do Estado do Espírito Santo - Silva, Pedro Paulino da (2014)
This research analyzed the resistances to the History curriculum to the high school prescribed by the State Department of Education from Espírito Santo (Sedu) in 2009 to be developed in its teaching network by the teachers at this stage of basic education. The objective was to investigate the causes of the resistances fixed in the curriculum document and to identify what teachers resist, why they are resisting and how they are materializing their resistances to it. Resistance, means the set of activities carried out by teachers announced in the form of opposition, in an attempt to stop the domination and not lose their identities. A conscious resistance, despite rejecting, does not deny the curriculum. Although, it does not submit passively to it, implies a position to reclaim its reworking, its reinvention. For theoretical context, we discussed concepts and perspectives of the curriculum, resistance, high school and their relations with education. The project is located in the education area, in the research area of Culture, Curriculum, and Training for Educators. The research is a qualitative one and we relied on narrative research as a methodological approach. As methodological procedures, we relied on documents and literature analysis, application of pre-structured questionnaire and observations and conversations with four high school history teachers in the city of Afonso Cláudio, State of Espírito Santo. With the collation of the data produced, the assumption presented in this work was confirmed. As generative dimensions of resistance, were evidenced the prescription, whereas teachers believe this to be their attribution, along with the school; the content organization presented by SEDU; the nonlinearity of historical events; the provision of the knowledge by themes; guidance for interdisciplinary work, the disassociation of the contents of each grade / year in the schoolbook; and the bureaucratic demand with the deployment of the curriculum. The contribution of labor to the State Education Network of resistance was problematization to the curriculum, educational artifact that can produce stability and tension between the subjects involved, and may be useful for further discussions. For educators, the work was relevant for having promoted space for debates about the curriculum of the high school history during the conversations at school.